Nocardia Detection in Respiratory Samples Using Targeted Next-Generation Sequencing: Cautious Interpretation Is Necessary for Timely Discovery - Chaowen Deng; Simon Kam-Fai Lo; Kelvin Hei-Yeung Chiu; Fanfan Xing (Infectious Microbes & Diseases)
Abstract. The expanding application of targeted next-generation sequencing (tNGS) in clinical diagnostics has led to an increasing frequency of Nocardia spp. detection in respiratory specimens; however, the clinical relevance and interpretation of these findings remain uncertain. This study describes the epidemiology of Nocardia pneumonia and colonization in patients at The University of Hong Kong–Shenzhen Hospital, China, and evaluates the diagnostic role of tNGS. The analysis was conducted from January 2023 through December 2024 and included 22 patients in whom Nocardia spp. were detected in respiratory specimens via tNGS. Among these patients, 81.8% (18/22) had comorbidities, most commonly chronic lung disease (40.9%, 9/22). Common clinical symptoms included cough, sputum and fever. Nocardia farcinica and Nocardia abscessus were the predominant species identified. Although the median number of sequence reads of Nocardia were higher in infected patients than in colonized individuals (289, IQR: 132.5–3747 vs. 133.5, IQR: 51.75–261.3), the difference was not statistically significant (P >0.05). In a comparison of diagnostic performance, tNGS identified Nocardia sequences in all 25 respiratory samples collected from the enrolled patients, whereas conventional aerobic culture successfully isolated the pathogen in only two patients. Additionally, tNGS exhibited a significantly shorter median turnaround time than culture (38 h vs. 376.5 h). These findings highlight tNGS as a rapid tool for Nocardia detection. However, the final diagnosis of nocardiosis cannot rely solely on sequence read thresholds. Clinical, radiological and laboratory integration remains critical in distinguishing true infection from colonization, ensuring accurate diagnosis and management of nocardiosis.